First record of the common sun star Crossaster papposus (L., 1767) in the Baltic Sea in over 100 years - Romoth Katharina; Gogina Mayya; Beisiegel Kolja; Darr Alexander; Zettler Michael Lothar (Oceanological and Hydrobiological Studies)
The rare in the German North and Baltic Sea waters and strictly protected sea star Crossaster papposus was found in 2019 and 2021 during monitoring activities in a marine protected area. This unique observation was achieved by using towed camera platform imagery along a transect in the Fehmarn Belt, which allows monitoring of a much larger area of the seafloor compared to traditional invasive grab and dredge sampling. The last time C. papposus was documented in this area was in 1871, indicating the rarity of this species in the Baltic Sea. Possible explanations for such rare records of the occurrence of this presumably native species in the study region are briefly discussed, including uncommon survival due to salinity conditions caused by prior inflows of saline water from the North Sea.